PENGARUH PENGETAHUAN AKUNTANSI, SOSIALISASI STANDAR AKUNTANSI DAN SKALA BISNIS TERHADAP KUALITAS LAPORAN KEUANGAN EMKM - Blathasar Malindar; Felry Agustina Sairmaly; Johanis Nifanngeljau; Paulus Laratman (Jurnal Akuntansi Trisakti, 2023)
The purpose of this study is to determine the effect of accounting knowledge, socialization of SAK EMKM and scale of business on the preparation of financial statements which are based on the EMKM Financial Accounting Standards in the Tanimbar Islands. In this research, the data used are primary and secondary data. The population that will be used in this research is 69 SMEs. While in determining the sample using the sampling technique is total sampling, therefore the number of population that will be sampled, so it can be seen that the number of samples that will be used in this research is 69 MSMEs in the Tanimbar Islands. The data collection technique used in this research is a questionnaire. The data analysis technique used is using multiple linear regression analysis which will be assisted by using SPSS 26 software. The results found in this research are that accounting knowledge and socialization of SAK EMKM have no effect on the preparation of financial statements of EMKM Financial Accounting Standards, while on a business scale it has an effect on preparation of financial statements of EMKM Financial Accounting Standards